Efficient perovskite titanate photocatalysts for oxygen evolution reactions. (2021) - Paramanik, Lekha; Parida, Kulamani
Abstract: Exploring titanate based perovskites to harness solar energy represents a very significant interest in the field of photocatalysis. Unique properties of activation under light irradiation, tunable band gap energies with extraordinary photostability craft perovskite titanates as an efficient semiconductor photocatalyst for photocatalytic performance. Herein, highly active and stable perovskite titanates such as PbTiO3, CoTiO3 and BaTiO3 were synthesized through a simple low cost citric gel method. The as-synthesized phototocatalysts were well characterized by X-ray diffraction (XRD), Ultra violet Spectroscopy and Photoluminescence techniques. The results revealed that CoTiO3 exhibited an excellent photocatalytic performance towards oxygen evolution and multiple reproducible characteristic features under visible light illumination. The highest oxygen evolution yield was up to 98.12 μmol/h. The high photocatalytic activity toward O2 evolution is due to minimal recombination rate of photogenerated charge carriers in the material, as elucidated from photoluminescence spectroscopy analysis. Overall, the present work may provide a new reference for the fabrication of various high-quality perovskite titanates, promoting their potential for different photocatalytic applications.